2010
DOI: 10.1007/s11033-010-9965-9
|View full text |Cite
|
Sign up to set email alerts
|

α-Dystrobrevin distribution and association with other proteins in human promyelocytic NB4 cells treated for granulocytic differentiation

Abstract: Keywords:Alpha-dystrobrevin, Histone deacetylase inhibitor, BML-210, retinoic acid, granulocytic differentiation. Abbreviations used:-DB, alpha-Dystrobrevin; ATRA, all-trans retinoic acid; HDACI, histone deacetylase inhibitor. AbstractDystrobrevins bind directly to dystrophin and are prominent components of the dystrophin-associated protein complex that links the cytoskeleton to the extracellular matrix. They are involved in brain development, synapse formation and plasticity, as well as water and ion homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, its binding proteins and mediated pathway are not sufficiently understood. A protein's binding partners and its involved networks are keys to describing its mediated pathway and to understanding the complex cellular biological processes involved [4-7]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its binding proteins and mediated pathway are not sufficiently understood. A protein's binding partners and its involved networks are keys to describing its mediated pathway and to understanding the complex cellular biological processes involved [4-7]. …”
Section: Introductionmentioning
confidence: 99%
“…Tropomyosin and its multiple isoforms stabilize and regulate actin cytoskeletal dynamics [25,26]. We and others [19,[27][28][29] demonstrated that various proteins of DAPC like α-DB and dystrophin Dp71 might be involved in cytoskeleton reorganization [19], nuclear envelope [27] and nuclear matrix architecture [28,29] not only in muscle (C2C12) but also in non-muscle cell lines (NB4, HeLa and PC12). This certify the possibility of DAPC members to participate in signal transduction and modulation of processes for cell functioning.…”
Section: Discussionmentioning
confidence: 86%
“…Recently we identified [19] α-DB-interacting proteins involved inter alia and in cytoskeleton reorganization (actin, tropomyosin, gelsolin, tubulin) during proliferation and differentiation of human promyelocytic leukemia NB4 cells. Incidentally, we have preliminary evidence the silencing of α-DB, strongly affects the structure of F-actin cytoskeleton in adherent HeLa cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Although a-DB is a well-characterized dystrophin-related protein involved in cell signaling, its recently shown nuclear localization [Kulyte et al, 2002;Fuentes-Mera et al, 2006;Gonzalez-Ramirez et al, 2008;Borutinskaite et al, 2011;Navakauskiene et al, 2012], as well as the generation of multiple isoforms by alternative splicing of the a-DB gene [Blake et al, 1996], may expand the functional diversity of the protein. Nuclear environment may confer on a-DB the capability to assemble into new protein complexes that are involved in specific nuclear roles; consistent with this, we previously showed that a-DB1 is involved in the maintenance of nuclear morphology through association with nuclear envelope protein lamin B1 [Aguilar et al, 2015] In this study, we continue with the identification and characterization of nuclear function(s) for a-DB using N1E115 neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, α‐DB has previously been shown to localize to the nucleus of different cells lines [Fuentes‐Mera et al, ; Gonzalez‐Ramirez et al, ; Borutinskaite et al, ; Kulyte et al, ; Navakauskiene et al, ], which might implicate this protein in nuclear processes. The nucleus is a highly dynamic organelle that is organized into distinct, membrane‐free compartments to coordinate the execution major cellular events, including messenger RNA (mRNA) synthesis and processing, ribosome subunit biogenesis, and DNA replication.…”
mentioning
confidence: 99%